Confronting global climate change : experiments and applications in the tropics - Harris, Mark (Mark Anglin) (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This book offers a solutions-based approach to climate change problems which potentially impinge on human beings within the tropics. It largely comprises research articles with supplementary applications and illustrations. The effects of atmospheric phenomena, energy acquisition, wind power, CO2 sequestration, are linked with soils, aquatic life, reducing deforestation, rainwater harvesting and clay pot farming, climate, plant disease and food security to show that no area of life is untouched by the phenomenon of climate change. It discusses specific problem areas and provides an overview of geotechnical and sustainable solutions to lessen the impact of climate.
OCLC-licensed vendor bibliographic record.
Keywords: Climate change mitigation -- Tropics; Environmental protection -- Tropics; Tropics -- Climate; BUSINESS & ECONOMICS / Infrastructure; SOCIAL SCIENCE / General; SCIENCE / Environmental Science; TECHNOLOGY / Environmental Engineering & Technology